The Development of Sociocultural Malay-Based on Folklore Teaching Materials for Class X at SMA N 1 Percut Sei Tuan Deli Serdang - Junifran Junifran; Rosliani Rosliani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine the results of the development of sociocultural-based folklore teaching materials in class X at SMA Negeri 1 Percut Sei Tuan. SMA Negeri 1 Percut Sei Tuan is a public school in the city of Medan and is located in Percut Sei Tuan Village. The teaching materials developed are modules. This research is a development research based on the development model from Borg and Gall. The subjects consisted of material experts, design experts, Indonesian language teachers, and class X students of SMA Negeri 1 Percut Sei Tuan. The results showed that (1) the sociocultural values contained in the folklore of Putri Hijau and Hikayat Si Khalib include, (a) religious values, (b) solidarity values, (c) the value of unity, (d) the value of struggle, and (e) cultural values. (2) Validation from material experts includes the feasibility of content getting 92.68% in the "very good" category, 94.19% presentation eligibility acquisition in the "very good" category, and 93.13% language eligibility acquisition in the "very good" category. The validation from design experts with an average of 81.81% with "good" criteria. Overall, the teacher responses with an average of 92.26% on the "very good" criteria. Individual trials with an average percentage of 75.6% with the criteria "good enough". Small group trials with an average percentage of 83.77% with "good" criteria, and limited field trials with an average percentage of 91.80% with "very good" criteria. (3) The results of learning to rewrite folklore before using the module obtained 61.97%, while the learning outcomes of the folk tale rewriting test after using the module obtained 82.40%. The difference obtained is 18.58% from before and after using the module. This proves that the folklore teaching materials based on the sociocultural Malay are increasing.